The Five Finger Relaxation Techniques on Pain and Sleep Quality In Rhematic Patients In Sukabumi Village, Working Area Of The Selabatu Health Center, Sukabumi City - Rosliana Dewi; Nurani, Meilani Dwi; Fatmala, Syiva Dwi; Wahida, Astri Zeini; Budhiana, Johan; Arsyi, Dila Nurul (Alta Dharma Publisher, 2022)
Background: Rheumatism is a common disease among the elderly that can cause pain and interfere with quality sleep. The five-finger relaxation technique is a non-drug treatment for these symptoms. Objective: This study aims to determine the effect of the five-finger relaxation technique on pain and sleep quality in the elderly with rheumatism. Method: a quasi-experimental pre- and post-test with non-equivalent control group was applied in this study. The samples were 30 elderlies with rheumatism, which is divided into control and intervention groups. Result: There were differences in the pre-test and post-test scores on pain (p = 0.000) and sleep quality (p = 0.041) in the control group, and pain (p = 0.000) and sleep quality (p = 0.001) in the intervention group, and there were differences in scores. pain (p = 0.009) and sleep quality (p = 0.007) in the control group and the intervention group. The intervention group scored better than the control group. Conclusion: Five-finger relaxation causes effects such as relaxation, inner peace, peace, joy, to reduce mental stress and tension, which ultimately causes pain relief and improves sleep quality for the elderly with rheumatism. There is an effect of five-finger relaxation techniques on pain and sleep quality in the elderly with rheumatism. Recommendation: It is expected that the relaxation of the five fingers will become a form of independent nursing intervention for a nurse in providing nursing care for rheumatic patients. Keywords: Five Finger Relaxation Technique, Pain, Rheumatism, Sleep Quality